2022
DOI: 10.1073/pnas.2117090119
|View full text |Cite
|
Sign up to set email alerts
|

Specialization of the photoreceptor transcriptome by Srrm3 -dependent microexons is required for outer segment maintenance and vision

Abstract: Retinal photoreceptors have a distinct transcriptomic profile compared to other neuronal subtypes, likely reflecting their unique cellular morphology and function in the detection of light stimuli by way of the ciliary outer segment. We discovered a layer of this molecular specialization by revealing that the vertebrate retina expresses the largest number of tissue-enriched microexons of all tissue types. A subset of these microexons is included exclusively in photoreceptor transcripts, particularly in genes i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Count of nuclei in ONL was performed on three eyes/genotype (at least two sections per eye) at p30. Only sections in which the optic nerve was contained were used, and two images from each section were photographed under a Leica DM‐5500 microscope, with the objective Leica ∞/0.17/D, HCX PL FLUOTAR, 40×/0.75 that acquires an area of 0.31 mm 2 , in comparable regions equidistant from the optic nerve head (Barbato et al , 2017; Karali et al , 2020; Ciampi et al , 2022; Intartaglia et al , 2022). The acquired images were used for nuclei counts.…”
Section: Methodsmentioning
confidence: 99%
“…Count of nuclei in ONL was performed on three eyes/genotype (at least two sections per eye) at p30. Only sections in which the optic nerve was contained were used, and two images from each section were photographed under a Leica DM‐5500 microscope, with the objective Leica ∞/0.17/D, HCX PL FLUOTAR, 40×/0.75 that acquires an area of 0.31 mm 2 , in comparable regions equidistant from the optic nerve head (Barbato et al , 2017; Karali et al , 2020; Ciampi et al , 2022; Intartaglia et al , 2022). The acquired images were used for nuclei counts.…”
Section: Methodsmentioning
confidence: 99%
“…This leaves a sizable population of photoreceptor-specific exons that rely on other factors for their splicing. Recent studies have highlighted two such factors, PCBP2 and SRRM3, that can either act independently or cooperate with Musashi to promote splicing of alternative exons in photoreceptors 42 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Some examples are RPGR and BBS8 , both causative of non-syndromic retinal ciliopathies when their mutations map in retina-specific exons exclusively present in photoreceptor isoforms [ 51 , 52 ]. Interestingly, a recent study showed that retina-enriched microexons are particularly present in genes involved in vesicle-mediated transport, cilium assembly, and ciliary trafficking [ 53 ]. USP48 has many annotated isoforms, but only the full-length protein has been studied so far.…”
Section: Discussionmentioning
confidence: 99%